2012
DOI: 10.1097/iae.0b013e31826956b7
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Ranibizumab Versus Bevacizumab for Treatment of Myopic Choroidal Neovascularization

Abstract: Intravitreal ranibizumab and IVB are effective in the treatment of subfoveal myopic choroidal neovascularization. Intravitreal ranibizumab achieved greater efficacy than IVB in terms of the mean number of injections administered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
2
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 31 publications
5
65
2
3
Order By: Relevance
“…In a recent prospective study with a follow-up of 18 months, Iacono et al [36] showed no difference between the two drugs regarding their ability to improve VA, confirming and expanding the preliminary results of Gharbiya et al [37]. However, ranibizumab displayed a greater effectiveness with respect to the mean number of injections required to achieve the same outcome [36].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In a recent prospective study with a follow-up of 18 months, Iacono et al [36] showed no difference between the two drugs regarding their ability to improve VA, confirming and expanding the preliminary results of Gharbiya et al [37]. However, ranibizumab displayed a greater effectiveness with respect to the mean number of injections required to achieve the same outcome [36].…”
Section: Discussionsupporting
confidence: 61%
“…In a recent prospective study with a follow-up of 18 months, Iacono et al [36] showed no difference between the two drugs regarding their ability to improve VA, confirming and expanding the preliminary results of Gharbiya et al [37]. However, ranibizumab displayed a greater effectiveness with respect to the mean number of injections required to achieve the same outcome [36]. In our study, the eyes were treated with both drugs; we cannot extrapolate the individual effect of each molecule, but our study suggests a clinical benefit from this class of drugs for the treatment of mCNV.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported good visual results for MO in BRVO with bevacizumab intravitreal therapy at 6 months and 1 year [5,6]. Bevacizumab was also reported to be as effective as ranibizumab in other diverse macular diseases [7,8,9,10]. Consequently, the latter was widely used off-label in France in BRVO treatment before February 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Similar data were found in the study by Cohen et al [25] with a mean intravitreal ranibizumab number of 3.5 (range 1–12) over a mean follow-up of 39.3 months. Pece et al [38] reported 2.3 intravitreal injections in the ranibizu­mab subgroup during 20-month follow-up; similarly, Iacono et al [16] reported a mean of 2.5 intravitreal rani­bizumab injections over 18 months. A 6-year analysis by Ruiz-Moreno et al [22] revealed a mean of 3.3 injections, and in the longest study of ranibizumab monotherapy for mCNV, Hefner and Gerding [31] performed a mean of 3.5 injections (range 1–12) during a mean follow-up of 85 months.…”
Section: Discussionmentioning
confidence: 99%